Spazio sacro nel De montibus di Giovanni Boccaccio - Bobay, Orsolya (Verbum – Analecta Neolatina, 2012)
The present paper discusses the various aspects of the religious places in Giovanni Boccaccio’s De montibus. First, we focus on the religious places of ancient Greek and Roman mythology, afterwards, those in the Bible. Finally, we will tackle the common features of all three. We will find that the most important places for Boccaccio were those mountains and the rivers that are connected to those holy places.